Determination of Aflatoxin Levels and Prevalence of Fungal Flora of Cwande Condiments Sold in Zuru Local Government Area, Kebbi State, Nigeria - Ahmad, A; Keta, J.N.; Singh, Dharmendra (Journal of Sustainability and Environmental Management, 2022)
Aflatoxins are group of secondary metabolites produced by certain mold species which are dangerous to humans and animals. Cwande is a local condiment that is used to add flavor to the food, it get infected with fungi and aflatoxins as a result of improper processing and storage procedures. This study aimed to determine the aflatoxin levels in Cwande condiments sold in Zuru Local Government Area, Kebbi State, Nigeria, as well as the prevalence of fungal flora. Twenty (20) dried processed samples from four different collection points in Zuru central market were chosen at random and placed in brand-new polythene bags. Fungi were isolated on Potato Dextrose Agar by Standard Dilution Plate method. Aflatoxin was determined using the ELISA method, which is enzyme-linked immunosorbent assay. Five fungal species were isolated and identified as Aspergillus flavus, A. niger, A. fumigatus, Rhizopus stolonifer and Fusarium Oxysporum. Fungal species were present in varying degrees, from 9.09% to 39.39%. Aflatoxins varied from 2.539 to 2.546 in all samples. These results led to the discovery that the commercially available Cwande in the Zuru central market was tainted with various fungal species, including aflatoxigenic ones. All of the samples tested positive for aflatoxin according to the analysis, however none of them had levels that exceeded the 10g/kg maximum permissible limit for humans stipulated by the EU and NAFDAC. More research should be conducted in order to determine the nutritional and anti-nutritional components of the regional condiment (Cwande).